The Ideality of the Kiai's Role in Practical Political Constellations - Nani Widiawati (HISTORICAL: Journal of History and Social Sciences, 2024)
This research aims to find a philosophical basis for the ideal position of kiai in practical political constellations. This study is a qualitative research with a literature study design and descriptive method focusing on finding the ideal concept of kiai in politics based on its reality dimensions. The research results show that kiai and politics in Islam are two things that are synergistic, kiai is a prototypical representation of the Prophet's heirs who appear as an active agent of social change, and the kiai's ideality in politics ultimately returns to the kiai's own consistency. In politics which is filled with intrigue and conflict, political leaders must be able to minimize conflict and act as problem solvers. If not, then religious positions can become instruments of power. Kiai must be able to realize his sociological role as agent of change consistently because politics is not just a tool of power but the science of how to build universal benefit.